RELATIONSHIP OF FEMALE BROODSTOCK WEIGHT AND REPRODUCTIVE PERFORMANCE OF C. gariepinus (Burchell 1822) - Egwenomhe, M; Okonji, V. A. (Nigerian Journal of Fisheries, 2018)
Achieving optimum reproductive performance in female broodstock and production of high-quality fish seed is a major challenge in fish farming. Selection is one of the breeding practices implored to achieve this. This study investigates the relationship of different bodyweight of female broodstock on the breeding performance of Clarias gariepinus. The experiment, a completely randomized design (CRD) with treatment combinations based on the average weight of female broodstock sizes, had Treatment I (Small size 1000 g), Treatment II (Medium size of 1500 g), and Treatment III (Large size of 2500 g). Data collected include volume and weight of eggs, fecundity, fertilization and hatching rates, and growth of yolk sac fry. The Physico-chemical parameters of the water had no significant (p>0.05) fluctuations. Treatment III had significantly (p<0.05) better spawning performance; with bigger eggs (32.67g/10 ml of eggs), highest fertilization rate (80.63%), hatching rate (88.90%), and survival rate of fry (91.70%). However, the average number of eggs/kg of spawners (fecundity) was highest in Treatment I (13,884). Fertilization (70.9 and 72.00%) and hatchability (74.9 and 75.57%) were not significantly different (P>0.05) between Treatments II and Treatment I respectively. Yolk-sac fry survival was not significantly different among Treatments. It was concluded that spawning performance increased with increasing broodstock size.